Clinical Management of Secretion Retention in Critically Ill Patients who are Intubated and Mechanically Ventilated - P. Berry, Marc; Marti, Joan-Daniel (Current Respiratory Medicine Reviews, 2014)
Secretion retention is common in critically ill patients who are intubated and mechanically ventilated. Due to the presence of an artificial airway, sedation and analgesia and alterations in the physiological mechanism through which humidification of inspired air occurs, secretion clearance is often impaired in this cohort of patients, Therefore, a bundle of non-pharmacological strategies are routinely used to manage airway secretion retention. This review paper explores several preventative strategies used in the management of airway secretions, offering a clinical perspective on their use in patients who are intubated and mechanically ventilated, based on current literature. Furthermore, this article discusses several treatment modalities, including chest physiotherapy techniques, which may be employed clinically to manage secretion retention, and the efficacy surrounding such techniques.
Keywords: airway secretion retention